1995
DOI: 10.1007/bf02633972
|View full text |Cite
|
Sign up to set email alerts
|

Organized type I collagen influences endothelial patterns during “spontaneous angiogenesis in vitro”: Planar cultures as models of vascular development

Abstract: Selected strains of vascular endothelial cells, grown as confluent monolayers on tissue culture plastic, generate flat networks of cellular cords that resemble beds of capillaries--a phenomenon referred to as "spontaneous angiogenesis in vitro". We have studied spontaneous angiogenic activity by a clonal population (clone A) of bovine aortic endothelial cells to identify processes that mediate the development of cellular networks. Confluent cultures of clone A endothelial cells synthesized type I collagen, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 39 publications
(69 reference statements)
6
86
1
1
Order By: Relevance
“…A daily administration of ACTH-(1-39) during 7 days fully restored plasma corticosterone level to control levels and partially restored adrenal weight from 5.4 Ϯ 0.62 mg (n ϭ 10) (DEX) to 7.5 Ϯ 0.5 mg (n ϭ 10), whereas the expression of the ACTH receptor was ϳ65% of the control value (P Ͻ 0.05). These results are consistent with in vitro observations demonstrating that ACTH receptor mRNA levels were stimulated by ACTH in cultures of human and bovine adrenocortical cells (32,48). All together, these data show that the glucocorticoid treatment of mice inhibits adrenal growth and steroid production, which gives an interesting model of hormonal regulation of the adrenal, because ACTH administration completely restored corticosterone production and stimulated adrenal growth.…”
Section: Vegf and Its Two High-affinity Receptors Flk-1/kdr And Flt-supporting
confidence: 91%
See 1 more Smart Citation
“…A daily administration of ACTH-(1-39) during 7 days fully restored plasma corticosterone level to control levels and partially restored adrenal weight from 5.4 Ϯ 0.62 mg (n ϭ 10) (DEX) to 7.5 Ϯ 0.5 mg (n ϭ 10), whereas the expression of the ACTH receptor was ϳ65% of the control value (P Ͻ 0.05). These results are consistent with in vitro observations demonstrating that ACTH receptor mRNA levels were stimulated by ACTH in cultures of human and bovine adrenocortical cells (32,48). All together, these data show that the glucocorticoid treatment of mice inhibits adrenal growth and steroid production, which gives an interesting model of hormonal regulation of the adrenal, because ACTH administration completely restored corticosterone production and stimulated adrenal growth.…”
Section: Vegf and Its Two High-affinity Receptors Flk-1/kdr And Flt-supporting
confidence: 91%
“…The growth of new vascular sprouts from existent vasculature is referred to as angiogenesis. The morphogenetic and regulatory processes that mediate and control an- (48). To determine whether steroidogenic cells could regulate endothelial cells in the adrenal cortex, we examined whether ACE cells exhibited changes in cellular morphology and orientation, which characterizes angiogenesis in vitro when cocultured with steroidogenic cells in 3D-collagen.…”
Section: Vegf and Its Two High-affinity Receptors Flk-1/kdr And Flt-mentioning
confidence: 99%
“…During angiogenesis, proliferating ECs are organized to form new 3-dimensional capillary networks through a process involving transition of endothelial precursor cells to spindleshape morphology in combination with alignment into solid, multicellular, precapillary, cordlike structures. Moreover, these cordlike structures are interconnected to form a polygonal network (18,19). Previous studies revealed that GTPase RhoA mediates cell contractility by organizing actin filaments into stress fibers; and active RhoA is required for a variety of complex morphogenetic processes, including embryonic gastrulation and epidermal wound healing (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The 3-dimensional type I collagen provokes ECs in culture to undergo marked shape changes that closely imitate precapillary cord formation in vivo (18). Therefore, we designed a strategy to investigate vascular morphogenesis by embedding ECs in collagen I to investigate the effects of RhoA on EC organizational behavior.…”
Section: Rhoa Expression On the Pegfp-c1-mentioning
confidence: 99%
“…38,41 In addition, highly invasive melanoma cells have been demonstrated to contract floating collagen gels. 42 Because we observed that highly invasive melanoma cells could generate patterned vessels in vitro, we explored the ability of these cells to contract floating matrices as evidence of their matrix remodeling potential.…”
Section: Biomechanical Potential Of Highly Invasive and Poorly Invasimentioning
confidence: 99%